Experimental Investigation on the Hydraulic Characteristics of the Two-Phase Flow in the Intersecting Rock Fractures - Chen Wang; Lujie Zhou; Yujing Jiang; Xuepeng Zhang; Jiankang Liu (Geofluids)
An appropriate understanding of the hydraulic characteristics of the two-phase flow in the rock fracture network is important in many engineering applications. To investigate the two-phase flow in the fracture network, a study on the two-phase flow characteristics in the intersecting fractures is necessary. In order to describe the two-phase flow in the intersecting fractures quantitatively, in this study, a gas-water two-phase flow experiment was conducted in a smooth 3D model with intersecting fractures. The results in this specific 3D model show that the flow structures in the intersecting fractures were similar to those of the stratified wavy flow in pipes. The nonlinearity induced by inertial force and turbulence in the intersecting fractures cannot be neglected in the two-phase flow, and the Martinelli-Lockhart model is effective for the two-phase flow in intersecting fractures. Delhaye’s model can be adapted for the cases in this experiment. The turbulence of the flow can be indicated by the values of C in Delhaye’s model, but resetting the appropriate range of the values of C is necessary.